2020
DOI: 10.1007/s40266-020-00796-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Orthostatic Hypotension: Beyond Anti-Hypertensive Medications

Abstract: Orthostatic hypotension (OH) is an abnormal blood pressure response to standing, which is associated with an increased risk of adverse outcomes such as syncope, falls, cognitive impairment, and mortality. Medical therapy is one the most common causes of OH, since numerous cardiovascular and psychoactive medications may interfere with the blood pressure response to standing, leading to drug-related OH. Additionally, hypotensive medications frequently overlap with other OH risk factors (e.g., advanced age, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 135 publications
(233 reference statements)
0
82
2
2
Order By: Relevance
“…We also noticed that only the participants with higher SBP (>144 mmHg), but not those with lower SBP, had an increased risk of cardiovascular mortality. The potential for side effects with antihypertensive therapy in oldest old had been noticed for a long time, including orthostatic hypotension, 20 accelerated cognitive decline, 21 and etc Although the aggressive BP lowering in the SPRINT trail did reduce the risk of cardiovascular events and all‐cause mortality in robust elders, the incidence of kidney injury and syncope were still high. The PARTAGE study found that the institutionalized individuals older than 80 years who were with lower SBP and under the treatment with 2 or more BP‐lowering agents resulted in a higher risk of mortality 22 .…”
Section: Discussionmentioning
confidence: 99%
“…We also noticed that only the participants with higher SBP (>144 mmHg), but not those with lower SBP, had an increased risk of cardiovascular mortality. The potential for side effects with antihypertensive therapy in oldest old had been noticed for a long time, including orthostatic hypotension, 20 accelerated cognitive decline, 21 and etc Although the aggressive BP lowering in the SPRINT trail did reduce the risk of cardiovascular events and all‐cause mortality in robust elders, the incidence of kidney injury and syncope were still high. The PARTAGE study found that the institutionalized individuals older than 80 years who were with lower SBP and under the treatment with 2 or more BP‐lowering agents resulted in a higher risk of mortality 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Factors including physical inactivity and peripheral vascular disease predisposing to peripheral venous pooling in addition to dehydration as a result of recent acute illness or medication such as diuretics may influence symptom prevalence in geriatric rehabilitation inpatients. 9,32,38 Conversely, asymptomatic OH may be indicative of adequate cerebral perfusion autoregulation on change in posture 11,39 or habituation to orthostatic intolerance symptoms. 40 Moreover, symptoms experienced by inpatients without OH may have corresponded with initial OH or rapid changes in blood pressure, 41 which can be accurately detected only by continuous blood pressure monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…44 Hospitalized inpatients typically take a higher number of medications, contributing to OH and symptoms. 9 Frequently prescribed cardiovascular and psychotropic medications in older adults commonly cause side effects of OH and orthostatic intolerance symptoms to prevail. 43,45 Lack of association between cardiovascular and psychotropic medication and OH or symptoms may indicate adequate blood pressure management of inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenic and non-neurogenic factors can cause orthostatic hypotension. Drugs, especially antipsychotics, are the most common cause of nonneurogenic orthostatic hypotension 10 . Antipsychotics that can cause orthostatic hypotension are considered antipsychotics that act on α-1 postsynaptic receptors like typical antipsychotics 11 ; however, supporting data is still very limited.…”
Section: Introductionmentioning
confidence: 99%